"If I have to clean, I clean my own shop": Migrant entrepreneurship as a form of emplacement in times of crisis: The example of Italy. (April 2019) - Lintner, Claudia
This article analyses the relation between European economic crisis and immigration. It does so by analysing the establishment of migrants' entrepreneurship activities in Italy, and by looking at how these activities unravel subjects' agency in confronting constraining socioeconomic conditions and restrictive immigration laws. In this perspective, entrepreneurship should be understood as a possibility for transforming a person's own incorporated cultural capital into a resource and, consequently, into an opportunity for self-created work performance. Interpreting entrepreneurship as a personal response of migrants to the economic recession offers a new perspective in the existing literature on migrant entrepreneurship. Crisis, in this paper, is not seen as an abstract and supernatural phenomenon leading and controlling the capacity of individuals to act, but is understood as a constructed set of meanings comprising social interactions and relationships and consolidated within public discourses. This study is based on a qualitative-explorative research approach and was carried out in South Tyrol, Italy. For the data collection, different qualitative methods were used: narrative interviews, informal discussions and semi-structured interviews. Data analysis was based on the coding processes described within the Grounded Theory. As the results show, crisis as such represents, on the one hand, a critical moment of transition or transformation of normality and the constituted ways of acting and thinking and, on the other hand, it is perceived as a new opportunity to change individual behaviour and to initiate innovative counter-strategies that will maintain a person's capacity to act even in critical personal and structural situations. Nevertheless, showing resilience, which is powerful and leads to change, depends not only on personal motivational forces but also to given opportunity structures.